Pengaruh Metode Kooperatif TGT (Team Games Tournament) Menggunakan Media Puzzle terhadap Hasil Belajar Matematika - Shinta Dwi Handayani (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of this research is to know the effect of applying the TGT (Team Games Tournament) cooperative method through a medium of puzzle on the mathematics learning outcomes. The method used is an experimental method. The sampling is conducted using a simple random sampling technique, with samples of 40 students consisting of 20 students of an experimental class and 20 students of a control class. The analysis to test the research hypothesis is performed using the mean difference test (t-test), with the results of the hypothesis test showing that there is the effect of applying the TGT (Team Games Tournament) cooperative method through a medium of puzzle on the mathematics learning outcomes.